Solitary Fibrous Tumor: Case Report of Intrapulmonary Location - Adil Arsalane; Abdelfetah Zidane; Hicham Fenane; Amine Azami; Ismail Essadi; Abderrahim Raissi; Issam Lalya; Yacine Msougar (Case Reports in Oncological Medicine)
Solitary fibrous tumors are relatively rare neoplasms that commonly occur in the pleura, especially visceral pleura. However, an intrapulmonary site of this kind of tumors is even rarer. These tumors can be characterized by a heterogeneous evolution and have a benign or malignant behavior. Wide surgical resection is essential to cure the patient and to avoid recurrence. We present here the clinical, imaging, and histological features of a case with solitary fibrous tumor growing inside the lung.